Incidence of pesticides on the quality of Solanum Lycopersicum tomato in the supply of retail markets in the city of Lima, Peru - Montaño-Roldan, Victor Lenin (2023)
The objective of this research article was to describe the incidence of pesticides on the quality of Solanum Lycopersicum tomatoes in the supply of retail markets in the city of Lima, Peru, by consulting updated bibliographic sources related to the subject under study. The methodology used was documentary analysis, with a general descriptive and descriptive approach. The search for information was carried out by means of an initial selection based on the abstracts and titles of the available information, identifying potentially eligible articles in the different Google Scholar and SciELO databases. The population consisted of 25 documents registered under the format of articles/books consulted, selected through criteria, being conformed by a total of six (06) documents. It has been found in the bibliographic review that the use of pesticides in tomato, not only affects its quality, but also that of traders and the ecosystem itself; however, it was found that the expenses produced by the investment lead the farmer to look for mechanisms to increase his profit, such as the use of substances that can reduce the pests that naturally affect this type of vegetable. It was discovered that growers lack techniques for spraying, and that spraying is carried out profusely, as well as inadequate post-harvest vegetable handling techniques. Finally, it was determined that there are factors that are considered as determinants of tomato quality such as characteristics; firmness, durability, uniformity and area of origin; however, in most retail markets this denomination is identified more with commercial aspects.